2010
DOI: 10.1186/1742-4690-7-104
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin induces HIV-1 transcription inhibited by ferroportin

Abstract: BackgroundPhysiological regulation of cellular iron involves iron export by the membrane protein, ferroportin, the expression of which is induced by iron and negatively modulated by hepcidin. We previously showed that iron chelation is associated with decreased HIV-1 transcription. We hypothesized that increased iron export by ferroportin might be associated with decreased HIV-1 transcription, and degradation of ferroportin by hepcidin might in turn induce HIV-1 transcription and replication. Here, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 37 publications
(58 reference statements)
4
62
0
Order By: Relevance
“…HIV-1 replication requires cellular iron (27), and hepcidin, which causes cellular iron retention, enhances HIV-1 replication in vitro (28). Therefore, we considered whether hepcidin levels measured during early infection might predict later set-point plasma viral load, which is established following acute and early events and is a strong prognostic indicator for disease progression (29,30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 replication requires cellular iron (27), and hepcidin, which causes cellular iron retention, enhances HIV-1 replication in vitro (28). Therefore, we considered whether hepcidin levels measured during early infection might predict later set-point plasma viral load, which is established following acute and early events and is a strong prognostic indicator for disease progression (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…Hepcidin downregulates surface expression of ferroportin in both lymphocytes and macrophages (36,37), increasing iron availability in key cellular sites of HIV-1 replication. HIV-1 replication is iron dependent (27); accordingly, HIV-1 replication is enhanced, in parallel with decreased ferroportin and increased cellular iron following treatment of promonocytic THP1 cells, primary human macrophages, and primary CD4+ lymphocytes with hepcidin (28). Thus, elevated hepcidin, as well as reflecting inflammation, may also contribute to a cellular environment favoring HIV-1 replication.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined the effect of hepcidin on ferroportin Q248H expression in human embryonic kidney 293T cells that naturally express undetectable levels of ferroportin. 34 Cells were transiently transfected with plasmids expressing ferroportin Q248H, WT ferroportin or ferroportin C326Y, a mutant that is not sensitive to hepcidin. 34 The EGFP expression plasmid was Figure 1A, lanes 6, 7 and 8), ferroportin Q248H expression persisted following treatment with 0.01 and 0.03 mM hepcidin ( Figure 1A, lanes 2 and 3) and was only reduced by treatment with 0.1 mM hepcidin ( Figure 1A, lane 4).…”
Section: Myc-tagged Ferroportin Q248h Is Resistant To Physiological Cmentioning
confidence: 99%
“…34 Cells were transiently transfected with plasmids expressing ferroportin Q248H, WT ferroportin or ferroportin C326Y, a mutant that is not sensitive to hepcidin. 34 The EGFP expression plasmid was Figure 1A, lanes 6, 7 and 8), ferroportin Q248H expression persisted following treatment with 0.01 and 0.03 mM hepcidin ( Figure 1A, lanes 2 and 3) and was only reduced by treatment with 0.1 mM hepcidin ( Figure 1A, lane 4). In contrast, ferroportin C326Y expression persisted at all hepcidin concentrations with a slight reduction when hepcidin was added (Figure1A, lanes 10-12).…”
Section: Myc-tagged Ferroportin Q248h Is Resistant To Physiological Cmentioning
confidence: 99%
“…[7][8][9] In vitro studies also provided conflicting evidence linking iron with HIV progression. Higher cellular iron levels in HIV-infected macrophages are associated with increasing HIV transcription, 10,11 and treatment of monocytes with the iron chelator deferoxamine (DFO) decreased NF-jB and HIV-1 reactivation by oxidative stress. 12 However, another study found no change in NF-jB with iron chelation.…”
mentioning
confidence: 99%